What Happens After Supervisory Intervention? : Considering Bank Closure Options - Josefsson, Mats (IMF Working Papers; Working Paper ;, 2003)
Closures have been used to resolve problem banks in many countries in a wide range of economic circumstances, yet banking supervisors frequently defer intervention and closure. Avoiding the costs of disruption is the principal argument in favor of extraordinary measures, such as the use of public funds for recapitalization or forbearance, as alternatives to closing insolvent banks. Well-planned and implemented closure options can preserve essential functions performed by failing banks, mitigating disruption. Extraordinary measures to avoid closure should generally be avoided, but may be used in a systemic crisis to preserve some portion of a widely insolvent banking sector.